MANAJEMEN KURIKULUM DI SMP ISLAM AL-HIDAYAH - Siti Salmah Nurafifah; Siti Suhasri Ainun Fitri; Adi Rosadi (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Curriculum management is a crucial aspect in the management and development of educational curricula, which plays an important role in ensuring the successful achievement of educational goals. This article explores the basic concepts of curriculum management and emphasizes the urgency of implementing them in the contemporary educational context. Through a systematic and directed approach, curriculum management enables the formulation of clear educational goals, designing a cohesive curriculum structure, selecting relevant learning materials, as well as evaluating and adapting the curriculum that is responsive to student needs and the dynamics of current developments. The planned curriculum management process includes various steps, including educational needs analysis, strategic planning, implementation, monitoring, as well as curriculum evaluation and revision. By adopting effective curriculum management, educational institutions can improve the quality of learning, adapt teaching to developments in technology and science, and achieve optimal educational results. This article highlights that good curriculum management does not only focus on learning content, but also on developing teacher competence and active participation of all stakeholders in the educational process. Thus, implementing comprehensive and adaptive curriculum management is the key to facing educational challenges in the era of globalization and digitalization.